Vietnam : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation focuses on the financial sector and macroeconomic situation in Vietnam. The authorities adopted a stabilization package in February 2011 in response to increasing pressures on prices and the exchange rate in late 2010. Executive Directors commended the tightening of macroeconomic policies in 2011, which contributed to declining inflation, stabilizing the exchange rate, and a rebuilding of international reserves. Directors also recommended that monetary policy give priority to reducing inflation and rebuilding reserves further.